RANCANG BANGUN APLIKASI SISTEM INFORMASI PAJAK BUMI BANGUNAN - Shantika Martha, Ilhamsyah (SEMIRATA 2015, 2015)
Mandated by Law No. 28/2009 concerning: Local Taxes and Levies job .Therefore delegated authority Land and Building Tax (PBB) from central government to cities and counties is an obligation that must be done. As one of the problems facing PBB is to manage the taxpayer's level of awareness is still very low so that it becomes a major factor maximal reception area. The Local Government take over the PBB Â by setting the following requirements: Local regulations Land and Building Tax, had a database of land and buildings, human resources to manage the data, and applications that can serve PBB in information systems. With the expected implementation of PBB Information Systems Land and Building Tax collection can be performed more optimally, so that can sustainably improve land and building tax receipts. Keywords: Information Systems, Land and Building Tax, Local Tax